Sociology on the web : a student guide - Stein, S. D. (Stuart D.) (Routledge, 2003)
Sociology on the Web is directed at those who want to be able to access sociology Internet resources quickly and efficiently without needing to become IT experts. The emphasis throughout is on the location of high quality sociology Internet related resources likely to be useful for learning, teaching and research, from among the billions of publicly accessible Web pages. In addition to extensive coverage of topics relating to the efficient location of files and Web sites, Part III provides a substantial and annotated list of high quality resources likely to be of use to students of sociology.